IMPROVING DANCE LEARNING MOTIVATION WITH THE APPLICATION OF AUDIO VISUAL LEARNING MEDIA ONLINE (CAR in Class VII-A SMP N 2 in Simanindo Samosir, 2022) - Youmi Ayu Prima Sihaloho; Elindra Yetti; Nursilah Nursilah (Universitas Pendidikan Indonesia, 2022)
Learning motivation is an urge to move, direct, and maintain a person's behavior to act and do something when learning to achieve learning goals. The purpose of this study is to 1). Describe the process of applying audio-visual media to increase motivation to learn dance in class VII-A at SMP N 2 Simanindo, Samosir online. 2). Increasing the motivation to learn dance in class VII-A at SMP N 2 Simanindo, Samosir through online audio-visual media. This research uses classroom action research method using Kurt Lewin's action research design. Data collection techniques in this study were in the form of questionnaires and interviews using qualitative and quantitative descriptive data analysis techniques. The study was conducted on 18 students of class VII A at one of the junior high schools in Samosir. The results of the study there is an increase in student motivation to learn. This can be seen in the data obtained. In the pre-cycle, the percentage of student learning motivation was 43.19%, in the first cycle the percentage of student learning motivation was 53.44% in the aspect of student willingness and student interest in learning and in the second cycle the percentage of learning motivation was 70.00% student activity, responsibility and student achievement in understanding the material. The existence of further research that researchers want to continue is to create more varied learning with varied learning media so that the learning received by students is more interesting.